1995
DOI: 10.1002/1097-0142(19950315)75:6+<1545::aid-cncr2820751527>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and biodistribution of a mouse/human chimeric antibody directed against pancreatic cancer mucin

Abstract: Background. Nd2 is a murine monoclonal antibody (MoAb) directed against purified mucins of the human pancreatic cancer cell line SW1990. The authors previously reported promising results with Nd2 for immunotargeting pancreatic cancer. However, murine MoAbs induce human anti‐mouse antibodies (HAMAs), a serious problem for clinical use. Mouse/human chimeric antibodies may be less immunogenic and therefore reduce the incidence of HAMAs. In this study, the binding affinity, tumor specificity, biodistribution, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…But one case of TFP (patient; 13) was false positive in RAID with c-Nd2. While Nd2, in general, shows no reaction to tissues of normal pancreas (including pancreatic ducts, acinar cells and islet cells) and chronic pancreatitis, 5,11) this surgical specimen demonstrated positive reactivity to Nd2 on acinar cells surrounding the branch of the pancreatic duct with epithelial hyperplasia, which is an unusual finding in chronic pancreatitis. Hyperplasia of pancreatic ducts is usually found in cases of mucin-producing pancreatic tumor (particularly intraductal papillary adenoma) and cystadenoma, which have high malignant potential.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…But one case of TFP (patient; 13) was false positive in RAID with c-Nd2. While Nd2, in general, shows no reaction to tissues of normal pancreas (including pancreatic ducts, acinar cells and islet cells) and chronic pancreatitis, 5,11) this surgical specimen demonstrated positive reactivity to Nd2 on acinar cells surrounding the branch of the pancreatic duct with epithelial hyperplasia, which is an unusual finding in chronic pancreatitis. Hyperplasia of pancreatic ducts is usually found in cases of mucin-producing pancreatic tumor (particularly intraductal papillary adenoma) and cystadenoma, which have high malignant potential.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, we prepared mouse /human chimeric Nd2 (c-Nd2), which retains the high affinity and specificity to pancreatic cancer of murine Nd2 (m-Nd2). 10,11) The present study was carried out to investigate the clinical usefulness of c-Nd2 for preoperative diagnosis after labeling with 111 In, and its therapeutic potential for pancreatic cancer.…”
mentioning
confidence: 99%
“…In order to reduce the side effects resulting from HAMA production in clinical trials, we produced c-Nd2 and found that its specificity and affinity to pancreatic cancer are similar to those of m-Nd2. 16) Since other investigators have suggested that chimeric antibodies are similar or superior to murine antibodies in ability to mediate ADCC, in this study we examined pancreatic cancer cell cytotoxicity during MLTC with Nd2 in order to determine the extent of induction of ADCC by c-Nd2. Cytotoxicity during MLTC for pancreatic cancer cell lines was increased by incubation with c-Nd2 in an E/T ratio-and dose-dependent fash- To estimate the in vivo effect of ADCC induced by cNd2, we examined inhibition of subcutaneous xenograft tumor growth and determined the survival of orthotopically transplanted nude mice following intraperitoneal injection of c-Nd2.…”
Section: Discussionmentioning
confidence: 99%
“…The antigen-binding affinities of m-Nd2 and c-Nd2 were investigated by competitive radioimmunoassay and Scatchard analyses as described by Hirayama et al 16) Pancreatic cancer cell line The human pancreatic cancer cell lines RWP-1 (well differentiated adenocarcinoma), Capan-1 (moderately differentiated), SW1990 (well/ moderately differentiated), Capan-2 (moderately differentiated), Panc-1 (poorly differentiated), and MiaPaca-2 (undifferentiated) were cultured in high-glucose Dulbecco's modified Eagle's minimum essential tissue medium (DMEM; Nikken Biomedical Laboratory, Kyoto) supplemented with 10% fetal calf serum (FCS; Gibco, Grand Island, NY), 100 IU/ml penicillin (ICN Biochemicals, Costa Mesa, CA) 100 IU/ml streptomycin (ICN Biochemicals) and sodium pyruvate (ICN Biochemicals). These cells were used as target cells for cytotoxicity assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation